Variations in leaf respiration and photosynthesis ratio in response to air temperature and water availability among Mediterranean evergreen species - Catoni, Rosangela; Gratani, Loretta (Journal of Arid Environments, 2014)
Net photosynthesis (PN) and leaf respiration (RL) of the evergreen species co-occurring in the Mediterranean maquis in response to water availability and air temperature variations were analyzed. The results underlined that the ratio RL/PN of the considered species ranged from 0.15 ± 0.08 (in winter) to 1.32 ± 0.80 (in summer). Variations of RL and PN during the year were attested by the PCA which was carried out using leaf physiological and morphological traits of the considered species. In particular, Cistus incanus having the highest mean yearly PN and RL rates and low leaf mass area (LMA) and leaf tissue density (LTD), was furthest from the other species emphasizing its drought semi-deciduous habitus, the highest photosynthetic capability in favorable conditions (spring), but low tolerance to drought. Erica multiflora and Rosmarinus officinalis were characterized by the highest LMA and LTD, low PN rates in drought and the lowest PN ones in spring. Erica arborea, Pistacia lentiscus, Phillyrea latifolia and Quercus ilex had the highest drought tolerance. Arbutus unedo and Smilax aspera were close to this group despite lower RL rates during the year. The xeromorphic leaves of the considered evergreen species (i.e. high LMA and LTD) favor carbon gain profits over transpiration losses during drought, nevertheless, the high construction cost of these leaf type justifies the relatively high RL rates.
Keywords: Leaf respiration; Mediterranean evergreen species; Net photosynthesis; Ratio RL/PN